2002
DOI: 10.1002/ijc.10506
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of human papillomavirus in cervical cancer: A multicenter study in China

Abstract: Key words: human papillomavirus infection; cervical cancer, epidemiology; ChinaThere is strong epidemiologic evidence indicating that human papillomavirus (HPV) plays a central role in the etiology of cervical cancer. [1][2][3][4] The women positive for HPV DNA have a risk of developing cervical cancer 15-50 times higher than those without HPV DNA. 1,2,4,5 Although HPV infection is common among young women, only a small minority go on to develop cervical cancer. This situation was reviewed by a group of resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
73
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(83 citation statements)
references
References 26 publications
8
73
2
Order By: Relevance
“…The very low rate of HPV-16 infection in cervical cancer is contrary to the previous reports of high infection rate of this high risk type in different populations ( Table 2 ). 17,19,21 However, it is comparable to the results of some other studies. 13,18,22 The study of Castellsague in Mozambique 13 has shown that there may be differences in the dominant HPV types in different populations and regions.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The very low rate of HPV-16 infection in cervical cancer is contrary to the previous reports of high infection rate of this high risk type in different populations ( Table 2 ). 17,19,21 However, it is comparable to the results of some other studies. 13,18,22 The study of Castellsague in Mozambique 13 has shown that there may be differences in the dominant HPV types in different populations and regions.…”
Section: Discussionsupporting
confidence: 87%
“…In total, 87.1% of studied samples were positive for the presence of HPV DNA, which was comparable with the results of some previous studies in Danish, Belgian, Brazilian and Chinese patients. [17][18][19][20] Genotyping for HPV-16 and HPV-18 revealed that 26.7% of HPV positive samples were HPV-16 DNA positive, however, none of them were positive for HPV-18 DNA. The very low rate of HPV-16 infection in cervical cancer is contrary to the previous reports of high infection rate of this high risk type in different populations ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…The number of cases studied from Africa and Europe/North America was about half of the number studied from Central/South America and south Asia, and large regions such as China were not included. Thus, the prevalence of HPV-58, e.g., which has been reported to be high in China, 24 Korea 25 and some regions of Africa, 26 may be underestimated in our study.…”
Section: Discussionmentioning
confidence: 54%
“…The corresponding percentages in other IARC HPV prevalence surveys in different continents were 32.6% in Europe, 22.5% in Asia, 22.0% in Latin America, and 12.2% in Africa , making the proportion of HPV16-positive women in our present populationbased study among the highest recorded worldwide. In a study of 809 cervical cancer cases from four areas in China, a relatively high proportion (66.9%) were positive for HPV16 (Lo et al, 2002).…”
Section: Discussionmentioning
confidence: 99%